Pathogenic FBN1 variants in familial thoracic aortic aneurysms and dissections. Issue 6 (20th January 2016) - Regalado, E.S.; Guo, D.C.; Santos‐Cortez, R.L.P.; Hostetler, E.; Bensend, T.A.; Pannu, H.; Estrera, A.; Safi, H.; Mitchell, A.L.; Evans, J.P.; Leal, S.M.; Bamshad, M.; et al.
Abstract : Marfan syndrome (MFS) due to mutations in FBN1 is a known cause of thoracic aortic aneurysms and acute aortic dissections (TAAD) associated with pleiotropic manifestations. Genetic predisposition to TAAD can also be inherited in families in the absence of syndromic features, termed familial TAAD (FTAAD), and several causative genes have been identified to date. FBN1 mutations can also be identified in FTAAD families, but the frequency of these mutations has not been established. We performed exome sequencing of 183 FTAAD families and identified pathogenic FBN1 variants in five (2.7%) of these families. We also identified eight additional FBN1 rare variants that could not be unequivocally classified as disease‐causing in six families. FBN1 sequencing should be considered in individuals with FTAAD even without significant systemic features of MFS. Abstract :